A coerência local em textos expositivos ou argumentativos, produzidos em Língua Portuguesa por vestibulandos - Freitas, Mirella de Oliveira (2006)
The objective of the present research was to draw the profile of the students that try the university entrance exam at Universidade Federal de Uberlândia, Minas Gerais, discriminating and classifying the problems of local coherence, found in their compositions, according proposal of Van Dijk (1981) and Van Dijk and Kintsch (1983). The research examined a sample of 300 texts, chosen at random, with notes varying between 0 and 10, which had been corrected and had their flaws were quantified and classified, inside of a total of 19 criteria, distributed inside between four groups, to know: pragmatic incoherences (ambiguities; contradictions; flaws regarding the "situation" (appeal to the sentimentality, to the dialogue, for example); fails as for the degree of information; clarity lack in the exhibition of ideas; lack of continuity of the ideas; escape to the verisimilitude; inconsistent argument; escape to the proposed theme; passages that favor no-authorized inference; flaws in the argument / idea no developed), syntactic incoherences, stylistic incoherences and semantic incoherences. The quantitative and qualitative analysis of the results pointed that the producing of texts present larger difficulty as for the pragmatic aspect (50,2% of the flaws), in other words, they have difficulties to make themselves to be understandood by clear and objective constructions, linked to the proposed theme, which would take the reader to a conclusion, in defense or against a given idea. The investigation still showed that a great part of the students has difficulties in applying the grammar in the texts that they produce, what carted 29,1% of flaws as for the syntactic aspects. After the analysis and the discussion of the obtained data, we understood that the students that try the university entrance exam do not have satisfactory domain in the production of texts, as for the application of textual procedures and grammatical knowledge. Therefore, they do not associate semantic, pragmatic, stylistic and syntactic aspects.